2010
DOI: 10.3102/0162373710382655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Failing a High School Exit Exam on Course Taking, Achievement, Persistence, and Graduation

Abstract: The increasing use of state-mandated public high school exit exams is one manifestation of the current movement in U.S. public schooling toward more explicit standards of instruction and accountability. Exit exam requirements implicitly argue that raising the bar for graduation creates incentives both for students to work harder in school and for schools to increase their efforts for low-achieving students. Such incentives should most strongly affect the motivation of students who fail an exit exam the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 26 publications
4
56
0
Order By: Relevance
“…The increased standards and achievement raise the value of the diploma as a signal of graduates' ability, which improves the labor market and college application prospects of graduates by reducing informational asymmetries in the labor and college market. At the school policy level, the HSEE provides a means of measuring school performance, making schools accountable for teaching the material for which they are responsible Reardon, Arshan, Atteberry, and Kurlaender, 2010). The state can be sure that tested schools will work towards achieving the standards on which they are tested.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased standards and achievement raise the value of the diploma as a signal of graduates' ability, which improves the labor market and college application prospects of graduates by reducing informational asymmetries in the labor and college market. At the school policy level, the HSEE provides a means of measuring school performance, making schools accountable for teaching the material for which they are responsible Reardon, Arshan, Atteberry, and Kurlaender, 2010). The state can be sure that tested schools will work towards achieving the standards on which they are tested.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This supports the intuition that HSEEs may motivate students and help focus their efforts on mastery of relevant material, but also highlights the importance of designing an exam that measures relevant content. Reardon, Arshan, Atteberry, and Kurlaender (2010) examine the impact of failing an HSEE in 10 th grade-with two years remaining to pass before graduationand find that barely failing the exam has no effect on students' academic trajectories, course taking, or graduation probability except for the very lowest achievers. Those authors conclude that negative effects of HSEEs on graduation rates come exclusively from the very lowest achievers.…”
Section: Previous Findings On Exit Examsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the public (or politicians') call for more measures for educational accountability, the actual effects are mainly discussed normatively rather than reviewed empirically in educational discourse (Maag Merki 2010;Reardon, Arshan, Atteberry, & Kurlaender, 2010). For example, after conducting a meta-analysis, Holme and her colleagues (2010) concluded that a limited number of existing empirical studies show the inconsistent or inconclusive effects of exit examinations on teaching and learning.…”
mentioning
confidence: 99%
“…Other researchers claim that the exit examinations increase the consistency in curriculum and instruction, but teachers often focus on test preparation too much and reduce time for class discussions or creative activities (Gayler, 2005;Zabala & Minnici, 2007). Yet other researchers claim that an exit examination exacerbates education inequality and increases the dropout rate of low-income minority students (Dee & Jacob, 2007) while others say it has no effect (Reardon et al, 2010). Overall, research studies have found that the positive effects of compulsory graduation examinations on instructional practices are either inconclusive (Holme et al, 2010) or largely dependent on schools, individuals, subjects and states rather than the existence of the exit examination itself (Baumert & Watermann, 2000;Maag Merki, 2010;Vogler & Carnes, 2009).…”
mentioning
confidence: 99%